Observation on the Efficacy of Moxibustion Combined with Ear Acupoint Pressing Beans in Treating Patients with Phlegm Stasis Syndrome Vertigo - Caidan Liu; Huanwen Luo; Zhongying Wang; Hong Luo; Yanlan Yu (Emergency Medicine International)
Objective. The aim of this study is to investigate the efficacy of moxibustion combined with an ear acupoint pressing bean in the treatment of patients with phlegm stasis syndrome vertigo. Methods. 60 patients with vertigo identified as phlegm stasis syndrome who were hospitalized in our department from May 2020 to May 2021 were selected and divided into a control group and a treatment group of 30 cases each according to the random number method. The control group was treated with conventional treatment and care, and the treatment group was treated with moxibustion combined with ear acupressing beans on top of the conventional group. The treatment effects, the dizziness disorder inventory (DHI), Pittsburgh sleep quality index (PSQI), Hamilton anxiety score (HAMA), TCM symptom score, and blood flow parameters (left vertebral artery flow velocity (LVA), right vertebral artery flow velocity (RVA), and basilar artery flow velocity (BA)) of the two groups were compared with each other during and after the treatment. Results. After implementation, the treatment efficiency of the treatment group was higher than that of the control group, and the treatment group had lower PSQI, HAMA, and DHI scores as well as TCM symptom scores such as vertigo, head heavy as a wrap, chest tightness, and nausea and vomiting than the control group (P<0.05). In addition, LVA, RVA, and BA were all higher in the treatment group than in the control group after treatment (P<0.05). Conclusion. Moxibustion combined with ear acupoint pressing bean treatment can clearly improve patients’ sleep quality, psychological state, relieve patients’ various symptoms caused by vertigo, improve blood flow parameters, and have better efficacy in the treatment of phlegm stasis syndrome vertigo.